Hollywood remembrance and American war
1 online resource
Keywords: Hollywood Remembrance and American War addresses the synergy between Hollywood war films and American forms of war remembrance. Subjecting the notion that war films ought to be considered the war memorials of today' to critical scrutiny, the book develops a theoretical understanding of how Hollywood war films, as rhetorical sites of remembering and memory, reflect, replicate and resist American modes of remembrance. The authors first develop the framework for, and elaborate on, the co-evolution of Hollywood war cinema and American war memorialization in the historical, political and ideological terms of remembrance, and the parallel synergic relationship between the aesthetic and industrial status of Hollywood war cinema and the remembering of American war on film. The chapters then move to analysis of Hollywood war films - covering The Great War, World War II, The Korean War, The Vietnam War, The Cold War, and the wars in Afghanistan and Iraq - and critically scrutinize the terms upon which a film could be considered a memorial to the war it represents. Bringing together the fields of film studies and memory studies, this book will be of interest to scholars and students in not just these areas but those in the fields of history, media and cultural studies more broadly, too.